2009
DOI: 10.1007/s00296-009-1151-9
|View full text |Cite
|
Sign up to set email alerts
|

Male gender results in more severe lupus nephritis

Abstract: Gender may produce different characteristics in the manifestation of systemic lupus erythematosus (SLE). The present study investigated the influence of gender on clinical, laboratory, autoantibodies and histopathological classes of lupus nephritis (LN). As much as 81 patients diagnosed with SLE (ACR criteria) and active nephritis, who underwent renal biopsy between 1999 and 2004, and who had frozen serum samples and clinical data available from the time of biopsy, were selected for this study. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 19 publications
10
60
3
Order By: Relevance
“…Interestingly, in SLE, in which women are affected about 10 times more frequently than men, it is interesting to note that male gender has been associated with more severe disease and with higher prevalence of pathogenic anti-dsDNA autoantibodies (Freire de Carvalho et al, 2010;Lu et al, 2010;Molina et al, 1996). Similarly, RRMS affects women about twice as often as men, and overall male gender has also been associated with worse prognosis.…”
Section: -Discussionmentioning
confidence: 99%
“…Interestingly, in SLE, in which women are affected about 10 times more frequently than men, it is interesting to note that male gender has been associated with more severe disease and with higher prevalence of pathogenic anti-dsDNA autoantibodies (Freire de Carvalho et al, 2010;Lu et al, 2010;Molina et al, 1996). Similarly, RRMS affects women about twice as often as men, and overall male gender has also been associated with worse prognosis.…”
Section: -Discussionmentioning
confidence: 99%
“…Indeed, men with SLE seem to have a greater risk of developing LN, whether this is due to delayed diagnosis [64] or less aggressive treatment [65] is not yet clear. The long-term outcome in men with LN appears to be worse with men more likely to develop CKD than women [68] and more likely to have higher renal activity index [69]. Wang et al described 415 patients with biopsy-proven LN, of whom 45 were male, showing that men had a later diagnosis and worse renal function than their female counterparts [70].…”
Section: Gendermentioning
confidence: 99%
“…Findings of several studies have demonstrated that male SLE patients present a typical manifestation, tend to have a significantly worse prognosis and have more serious kidney involvement (41)(42)(43). More specifically, a recent study has addressed the gender-based differences in Brazilian lupus patients and demonstrated that male patients had more severe LN, as indicated by higher creatinine levels and by comparison of the histopathological activity index values when compared to females diagnosed with this renal abnormality (44). Moreover, by promoting the expression of nephritogenic gp70 autoantigen (45)(46)(47), TLR7 is involved in the acute phase expression of serum envelope glycoprotein gp70 in murine lupus.…”
Section: Discussionmentioning
confidence: 99%